Rough Sets: International Joint Conference, IJCRS 2021, Bratislava, Slovakia, September 19-24, 2021, Proceedings - Ramanna, Sheela; Cornelis, Chris; Ciucci, Davide (Lecture Notes in Computer Science, 2021)
The volume LNAI 12872 constitutes the proceedings of the International Joint Conference on Rough Sets, IJCRS 2021, Bratislava, Slovak Republic, in September 2021. The conference was held as a hybrid event due to the COVID-19 pandemic.The 13 full paper and 7 short papers presented were carefully reviewed and selected from 26 submissions, along with 5 invited papers. The papers are grouped in the following topical sections: core rough set models and methods, related methods and hybridization, and areas of applications.